Research on Sustainable Development Strategies for Folk Culture in Rural China: Based on the Experiencing Perspective - Ma, Pandong; Lu, Fenghua; Deng, Jiqun (Problemy Ekorozwoju, 2026)
This study explores sustainable development strategies for folk culture in rural China from the experiencing perspective, aiming to propose practical and context-specific pathways tailored to China's unique conditions. Rooted in rural communities, folk culture represents a significant component of Chinese cultural heritage and holds unique value across social, economic, and environmental dimensions, serving as a vital cultural resource for rural revitalization. However, as urban modernization progresses, folk culture faces challenges in transmission and innovation. By integrating the experiencing perspective with the inheritance and innovation of folk culture, and leveraging the rural revitalization strategy, this research examines sustainable development strategies and proposes multidimensional implementation pathways. These strategies include policy support, educational outreach, digital technology application, and integration with modern industries, promoting the continued transmission and development of folk culture in contemporary society.